Drosophila TRP channels and animal behavior. - Fowler, M.A.; Montell, C. (Life Sciences, 2013)
Multiple classes of cell surface receptors and ion channels participate in the detection of changes in environmental stimuli, and thereby influence animal behavior. Among the many classes of ion channels, Transient Receptor Potential (TRP) cation channels are notable in contributing to virtually every sensory modality, and in controlling a daunting array of behaviors. TRP channels appear to be conserved in all metazoan organisms including worms, insects and humans. Flies encode 13 TRPs, most of which are expressed and function in sensory neurons, and impact behaviors ranging from phototaxis to thermotaxis, gravitaxis, the avoidance of noxious tastants and smells and proprioception. Multiple diseases result from defects in TRPs, and flies provide an excellent animal model for dissecting the mechanisms underlying "TRPopathies." Drosophila TRPs also function in the sensation of botanically derived insect repellents, and related TRPs in insect pests are potential targets for the development of improved repellents to combat insect-borne diseases.